Peculiarities of playing actions using offensive tactics of the lithuanian mens' handball national team at the 15th world championship - Skarbalius, A.; Strielciunas, R. (Education. Physical training. Sport, 2000)
The aim of the study was to establish the pecularities of playing actions of the Lithuanian mens` handball national team and those of their rivals when using offensive tactics at the 15th world championship held in 1997. Tactical actions of the Lithuanian mens` handball national team were registered on the basis of the protocol worked out. In the analysis of tactical actions a computer-based programme (Skarbalius & Strielèiûnas, 1999) was applied. This programme makes evaluation of the indications obtained from 282 tactical actions used in offence possible. Matches of the Lithuanian national team with the Swedish national team that placed 2nd as well as with other handball elite teams of the world (Iceland, Yougoslavia, Japan, Algeria) were registered and analysed. First and second half-times in six matches played by national teams of other countries, i.e. Japan, Egypt, Norway, Spain, Iceland, France, Croatia, Argentina and Cuba, taken at random were registered too. The general efficiency of attacks undertaken by the Lithuanian national team (43.85%) is by 1 per cent lower than of the national teams of other countries (44.85%), whereas the efficiency of positional attacks is the same (42%). Fast breaks of the Lithuanian national team (57.27%) were by 1.43 % more effective than those carried out by the national teams of other countries (55.84%). The attacks of the Lithuanian national team were the most succeccful (73.33%) when following unsuccessful fast breaks it continued offensive actions by positional means. The latter difference, however, is not statistically significant. The attacks undertaken by the Lithuanian national team were the most efficient during the first 20 sec. (44.94±9.27%) and in the interval between 45-60 sec. (45±27.39%). The efficiency of the attacks decreased (36.25±18.73%) when the duration of the attacks was 20-30 sec. And the duration of the attacks exceeding 60 sec (40±43.46%). The efficiency of attacks of the Lithuanian national team was the lowest (24.76±21.97%) when the rivals practised the defense system 6:0. In the case of the rivals practising other defence systems (5:1; 3:3; 3:2:1) the efficiency of the offensive tactics of the Lithuanian national team (43.85±7.66%) corresponded to the efficiency demonstrated by the national teams of other countries. The efficiency of attacks of the Lithuanian national team when playing in minority was lower by 11.57% though this difference was not statistically significant. The efficiency of team action in fast breaks of the Lithuanian national team was as much as 16.92 % lower than that shown by the national teams of other countries. The comparative analysis of tactical actions of the Lithuanian national team and the national teams of other countries has shown that the efficiency of the offence tactics of the Lithuanian national team at the 15th world championship corresponded to the standards demonstrated by others teams, participants of the championship. The Lithuanian national team, however, yields to national teams of other countries in the dynamism of the game and activity in the modern game handball prevailling the Lithuanian national team should develop a faster and more play in the 6-9 metre zone.